2017
DOI: 10.1080/0284186x.2017.1374557
|View full text |Cite
|
Sign up to set email alerts
|

Screening for psychological distress before radiotherapy for painful bone metastases may be useful to identify patients with high levels of distress

Abstract: Background: Psychological distress (PD) has a major impact on quality of life. We studied the incidence of PD before and after radiotherapy for painful bone metastases. Furthermore, we aimed to identify factors predictive for PD. Methods: Between 1996 and 1998, the Dutch Bone Metastasis Study included 1157 patients with painful bone metastases. Patients were randomized between two fractionation schedules. The study showed a pain response of 74% in both groups. Patients filled out weekly questionnaires for 13 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The study showed that 57.7% of patients experienced distress, and this was in line with the prevalence reported in previous reviews (ranging from 19% to 68.8%) [16,20,21]. The result was also in line with the observation of Westhoff et al [22], showing that 27% of metastatic bone tumor patients experienced high distress, while 29% experienced moderate distress. The potential distress in metastatic spinal tumor patients could be attributed to the late-stage tumor phase, accompanied by uncertainty about the future, concerns about physical disabilities, and treatment plans.…”
Section: Discussionsupporting
confidence: 91%
“…The study showed that 57.7% of patients experienced distress, and this was in line with the prevalence reported in previous reviews (ranging from 19% to 68.8%) [16,20,21]. The result was also in line with the observation of Westhoff et al [22], showing that 27% of metastatic bone tumor patients experienced high distress, while 29% experienced moderate distress. The potential distress in metastatic spinal tumor patients could be attributed to the late-stage tumor phase, accompanied by uncertainty about the future, concerns about physical disabilities, and treatment plans.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with advanced tumors suffer from bone pain and fracture due to the deterioration of tumors and bone metastases, causing bone cell absorption and osteolysis, or even bone destruction (4,5). Patients with bone metastases endure severe pain resulting in low quality of life and poor mental health, as well as loss of confidence in life (6). Morphine is a routine analgesic in the late stage of clinical treatment but with poor effect for patients with bone metastasis because of short onset time and side effects (7).…”
Section: Introductionmentioning
confidence: 99%